Bandwidth‐Efficient Selective Retransmission for MIMO‐OFDM Systems. Issue 1 (1st February 2015) - Zia, Muhammad; Kiani, Tamoor; Mahmood, Hasan; Shah, Tariq; Saqib, Nazar A.
Abstract : In this work, we propose an efficient selective retransmission method for multiple‐input and multiple‐output (MIMO) wireless systems under orthogonal frequency‐division multiplexing (OFDM) signaling. A typical received OFDM frame may have some symbols in error, which results in a retransmission of the entire frame. Such a retransmission is often unnecessary, and to avoid this, we propose a method to selectively retransmit symbols that correspond to poor‐quality subcarriers. We use the condition numbers of the subcarrier channel matrices of the MIMO‐OFDM system as a quality measure. The proposed scheme is embedded in the modulation layer and is independent of conventional hybrid automatic repeat request (HARQ) methods. The receiver integrates the original OFDM and the punctured retransmitted OFDM signals for more reliable detection. The targeted retransmission results in fewer negative acknowledgements from conventional HARQ algorithms, which results in increasing bandwidth and power efficiency. We investigate the efficacy of the proposed method for optimal and suboptimal receivers. The simulation results demonstrate the efficacy of the proposed method on throughput for MIMO‐OFDM systems.